BUILDING TRANSLATION NONCOGNITIVE AND SOCIAL SKILLS WITH PROJECT-BASED LEARNING: PROPOSAL AND STUDENTS’ OPINION - Sugeng Hariyanto; Achmad Suyono (Sean Institute, 2023)
There are many different translation theories and translation teaching theories. Knowledge of existing translation teaching methods or approaches will enrich teachers’ horizons, which will provide them with methods or approaches suitable to the situation. Professional skills that are essential for success in the workplace include technical skills, cognitive skills, noncognitive skills, and social skills. These skills theoretically could be built in the classrooms using appropriate translation teaching approaches, methods, designs, and procedures. However, there are not many discussions and publications on the development of teaching procedures that facilitate the building of noncognitive and social skills. This paper reports the implementation of project-based learning based on the empowerment approach to translation practicum courses at a private university in Indonesia to build noncognitive and social skills. The class creates groups of 5 students, and each adopts real translation companies' project management process. Thus, students, in turn, act as project managers, translators, and editors. The translation material is sought from the campus or outside sources. Based on the questionnaire collected from the students, it can be concluded that this class procedure improves students’ skills in negotiation, and teamwork, the testimony of one of the students, this approach improves students’ noncognitive and social skills.